Surgeons' Perspectives on User-Designed Prototypes of Microsurgery Armrests. (September 2018) - Abdelrahman, Amro M.; Lowndes, Bethany R.; Mohan, Anita T.; Noland, Shelley S.; Finnie, Dawn M.; Lemaine, Valerie; Hallbeck, M. Susan
Microsurgery is considered one of the most demanding surgical techniques. In a recent American Society of Reconstructive Microsurgeons survey, respondents reported that about half their procedures lasted 8 hours or longer and 8% had tremor during their surgery. Thus, the aim of this study was to define user centered design requirements for a microsurgery armrest, create low-fidelity armrest design concepts and evaluate microsurgeons' perspectives on the advantages/disadvantages of five potential design concepts. Direct and videotaped observations of microsurgery, user brainstorming during a co-creation workshop and semi-structured interviews were used. The resulting five microsurgery armrest concepts were presented pictorially through semi-structured interviews, where microsurgeons defined armrest design requirements as: a) an armrest that allows the surgeons to be as close as possible to the patient; b) adjustable to accommodate different procedures sites and surgeon preferences; c) rigid enough to support arms; d) is not difficult to set up; nor e) large or bulky; and f) complies with operative sterility rules. This study illustrated how involving the users (microsurgeons) early in the design process provides useful perspectives on design requirements and implementation barrier for a cost-effective ergonomic microsurgery armrest to foster sound ergonomic surgical practice and reduce musculoskeletal health risk factors during microsurgery.